Formulation and Evaluation of Delayed Release Coated Tablet of Dalfampridine for the Treatment of Multiple Sclerosis - Mhaskey, Yukta K.; P. Wankhade, Dr. Vikrant; Tikait, Aditi V.; C. Atram, Dr. Sandeep; Bobade, Nishant N.; Pande, Dr. S. D. (Asian Journal of Pharmaceutical Research and Development, 2024)
The study aimed to develop delayed release coated tablets of Dalfampridine for treating multiple sclerosis. Dalfampridine core tablets were prepared using wet granulation method with various excipients. Pre-compression parameters and flow characteristics were evaluated to ensure smooth tablet production. Post-compression studies included weight variation, thickness, hardness, friability, drug content, and In-vitro drug release. Coating was applied to the core table formulation using a 5% coating solution consisting of Eudragit L100-55, PEG-600, talc, color concentrate, IPA, and acetone. Coating parameters such as inlet temperature, spraying rate, and pan rotation were optimized using a 23 factorial design. The stability study confirmed the formulation’s stability at room temperature and 40°C/75% RH for one month. The coated tablets showed no drug release in acidic environments (pH 1.2) but released the drug in intestinal environments (pH 6.8). Formulation E2, coated under specific conditions i.e. inlet temperature of 500c, spay rate of 2ml/min and pan rotation of 15 rpm was identified as the best formulation based on % weight gain, coating process efficiency, and release time in the intestine.